Utilización de coxibs: una estrategia de intervención en la atención primaria Prescription of cyclooxygenase-2 inhibitors: an intervention strategy in primary care - Isabel Rosich; Maria Soler; Rosa Tomás; Dolors Crusat (Elsevier, 2005)
Objetivo: Evaluar una intervención dirigida a mejorar la prescripción de antiinflamatorios no esteroideos (AINE), fundamentalmente del grupo de los inhibidores de la ciclooxigenenasa-2 (coxibs). Sujetos y métodos: Estudio de intervención antes-después individual para médicos altamente prescriptores y grupal para el resto. Los datos sobre prescripción se obtuvieron del aplicativo de farmacia del Institut Català de la Salut. El período preintervención se comparó con el postintervención inmediato (que coincidió con la publicación de una alerta farmacológica sobre los efectos secundarios de los coxibs) y tardío. Se controlaron el gasto de coxibs, la dosis diaria definida (DDD) por 1.000 habitantes/día (DHD), el porcentaje DHD coxibs/total AINE, el porcentaje de AINE recomendados/total AINE, y el coste medio diario de la DDD de AINE. Resultados: La reducción media mensual del gasto en coxibs fue de 19.480 €/mes en el período postintervención inmediato y de 18.555 e/mes en el tardío. La disminución de la DHD de coxibs fue del 35,4% (p < 0,001), y fue estable en el tiempo. El porcentaje de AINE recomendados/total se incrementó un 14% a corto plazo y un 17% a largo plazo, mientras que el coste medio diario se redujo un 10,1 y 11,2%. La disminución de DHD de coxibs en los médicos entrevistados fue del 39,5% en el período inmediato y del 42,2% en el tardío, frente al 19,4 y al 12,4% en la intervención grupal. Conclusiones: La intervención educativa se asoció con una mejora en la prescripción de AINE, aunque la coincidencia con la alerta de seguridad limita la atribución causal a ésta. Objective: To evaluate an intervention designed to rationalize prescription of nonsteroidal anti-inflammatory drugs (NSAIDs), especially cyclooxygenase-2 inhibitors (COXIBs). Subjects and methods: We performed a before-after intervention study. Face-to-face educational outreach visits were conducted in general practitioners who were heavy prescribers and group intervention for the remaining. Data on prescribing habits were obtained from the pharmacy database of the Catalan Health Institute. The pre-intervention period (period 1) was compared with the immediate postintervention period (period 2, which coincided with the publication of a safety alert on the adverse effects of COXIBs) and the late postintervention period (period 3). The data monitored were: a) expenditure due to COXIBs; b) consumption in daily defined doses (DDD) per 1,000 habitants/day (DHD); c) the percentage of COXIBs/total NSAIDs and the percentage of recommended NSAIDs/total NSAIDs, and d) the mean daily cost of DHD of NSAIDs. Results: The mean monthly reduction in expenditure on COXIBs was 19,480 €/month in period 2 and was 18,555 e/month in period 3. The percentage of reduction in DHD of COXIBs was 35.4% (p < 0.001), which remained stable throughout the study. The percentage of recommended NSAIDs/total NSAIDs increased 14% in the short term and 17% in the long term while the mean daily cost was reduced by 10.1% and 11.2%. The decrease in DHD of COXIBs in the face-to-face intervention group was 39.5% in period 2 and was 42.2% period 3 compared with 19.4% and 12.4% in the group intervention. Conclusions: The educational intervention was associated with improvements in prescription of NSAIDs, although some of the improvement was probably due to the safety alert issued during the study period.